1997
DOI: 10.1136/adc.77.4.331
|View full text |Cite
|
Sign up to set email alerts
|

Cough sensitivity in children with asthma, recurrent cough, and cystic fibrosis

Abstract: In adults, cough sensitivity is influenced by gender and is heightened in those with non-productive cough. This study examined if cough sensitivity is (i) altered in children with asthma, recurrent cough, and cystic fibrosis and (ii) influenced by age, gender, or forced expiratory volume in one second (FEV 1 ).Cough sensitivity to capsaicin and spirometry were performed on 209 children grouped by the diagnosis of asthma, recurrent dry cough, cystic fibrosis, and controls.Cough sensitivity was increased in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 21 publications
2
60
0
2
Order By: Relevance
“…It is possible that rhinovirus infection could be responsible for persistent cough and BDR in susceptible subjects. This study has shown that, in addition to the observations of others of increased BHR and CRS at the time of coughing [17,23], there is also increased BDR. If BDR returns to normal when cough resolves, then a common reason for both BDR and cough would be suggested.…”
Section: Discussionsupporting
confidence: 76%
“…It is possible that rhinovirus infection could be responsible for persistent cough and BDR in susceptible subjects. This study has shown that, in addition to the observations of others of increased BHR and CRS at the time of coughing [17,23], there is also increased BDR. If BDR returns to normal when cough resolves, then a common reason for both BDR and cough would be suggested.…”
Section: Discussionsupporting
confidence: 76%
“…CHANG et al [26] have studied the cough-reflex sensitivity of boys and girls and found there is no sex-related difference. It is, therefore, possible that the greater sensitivity of the cough reflex seen in females arises after puberty.…”
Section: Discussionmentioning
confidence: 99%
“…With this technique, capsaicin concentrations (or other tussives such as citric acid and distilled water) are doubled until two and five "cough events" (typically defined by the number of expulsive events, or "cough sounds") are achieved, representing the threshold and suprathreshold response, respectively. These studies have shown differences in the cough response between ages [13], genders [14][15][16] and diseases [4,5,13,17]. However, these data cannot infer changes in expiratory muscle activation, duration of expulsive phases and the airflow dynamics with increasing capsaicin concentration, all which are essential components in defining the cough response.…”
Section: Introductionmentioning
confidence: 98%